2014
DOI: 10.1038/srep05342
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Photosensitizer-Based Contrast Agents for Photoacoustic Imaging

Abstract: Photoacoustic imaging is a novel hybrid imaging modality combining the high spatial resolution of optical imaging with the high penetration depth of ultrasound imaging. Here, for the first time, we evaluate the efficacy of various photosensitizers that are widely used as photodynamic therapeutic (PDT) agents as photoacoustic contrast agents. Photoacoustic imaging of photosensitizers exhibits advantages over fluorescence imaging, which is prone to photobleaching and autofluorescence interference. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 32 publications
3
102
0
1
Order By: Relevance
“…33 From the PA signal collected from the abdomen of the mice, maximum intensity projection images were obtained ( Figure 4B-E) and ROI analyses were performed on individual organs such as liver, spleen, kidney, and intestines. Figure 5A and B illustrate that the PA signal from the probe could be detected in the liver and spleen immediately after the injection of both folate-CP dots and CP dots and for up to a week.…”
mentioning
confidence: 99%
“…33 From the PA signal collected from the abdomen of the mice, maximum intensity projection images were obtained ( Figure 4B-E) and ROI analyses were performed on individual organs such as liver, spleen, kidney, and intestines. Figure 5A and B illustrate that the PA signal from the probe could be detected in the liver and spleen immediately after the injection of both folate-CP dots and CP dots and for up to a week.…”
mentioning
confidence: 99%
“…Using optical imaging for the indication of drug distribution needs to be carefully discerned, especially when imaging agents are physically integrated with the drug. Adopting new imaging modalities, such as fluorescence lifetime [66] and photoacoustic techniques [67,68], may further the application of hybrid nanocrystals for concurrent anticancer therapy and bioimaging.…”
Section: Hybrid Nanocrystalsmentioning
confidence: 99%
“…34 Due to its high optical absorption properties compared to endogenous chromophores in the body, PS are also good photoacoustic contrast agents. 89 Recently we demonstrated that PAI can map the heterogeneous accumulation of methylene blue (optical absorption peak around 670 nm) loaded liposomes in brain tumors to aid in personalized PDT dosimetry. 90 As active PDT agents, a concern is that PS could be photobleached during imaging procedures.…”
Section: Introductionmentioning
confidence: 99%